The USE OF SCAFFOLDING READING EXPERIENCE IN IMPROVING STUDENTS’ LITERACY DEVELOPMENT - Qushoy, Mohammad (STIT Buntet Pesantren Cirebon, 2022)
Literacy movement becomes the big issue todays in Indonesia. It has been raised because the level of literacy skills considered low. Consequently, it has led the teaching and learning second or foreign language becomes the important element in improving literacy skills especially through reading. The objective of this research was to get empirical evidence of the effectiveness of scaffolding reading experience in improving students’ literacy development. This research used quasi experimental method. The subjects were 55 students in a private Islamic Junior High School (27 Students for experimental class and 28 students for controlled class). Both of classes were given different treatment. Experimental class was taught by using scaffolding reading experience and the controlled class was taught using traditional way. The research conducted the procedure: pre-test, applying treatment and giving post-test. The result of this research showed significant effect performed by the students of experimental class which was treated by scaffolding reading experience. Their post-test mean score was greater than the posttest mean score of controlled class. In addition, the application of scaffolding reading experience is effective towards the students’ literacy development